The Role of Parents in Building Spiritual, Moral, and Intellectual Mentality in Children - Ahmad Fitriyadi Sari (Journal of Childhood Development, 2023)
This paper describes parents’ role in building mental spiritual, moral and intellectual children through approaches and methods. The presentation of this paper is based on the analysis of library data with a descriptive model.  From the results of the discussion, it can be concluded that the role of parents is the first and foremost educator for children, because it is from them that children first get basic education. Thus the first education obtained by children is from family life. Parent’s failure to foster children's morals to make them virtuous will not occur if they carry out their function or role as parents responsible for children. The presence of parents is very influential on children. Because obedience to children's religious, moral, and intellectual teachings is a habit that children learn in their family environment, parents must set a good example for their children. So that children can imitate what their parents have done